2018
DOI: 10.1021/acs.orglett.8b02526
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Aerobic Oxidative C–H/C–H Cross-Coupling of Unactivated Arenes for the Synthesis of Biaryls

Abstract: A mild and efficient protocol for the synthesis of 2,2'-difunctional biaryls from readily available benzamides and oximes by Co(OAc)·4HO catalysis has been developed. The catalytic cycle that includes aerobic oxidation of Co(I) to Co(III) is successfully achieved for the first time through dual-chelation-assisted C-H/C-H coupling with the assistance of catalytic Mn(acac). The catalytic system exhibits powerful reactivity and tolerates a large number of sensitive functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 57 publications
0
27
0
1
Order By: Relevance
“…Recently many studies have been dedicated to oxidative C−H/C−H cross‐coupling of arenes. The coupling is catalysed by different transition metal complexes including rhodium, ruthenium, platinum, gold, copper, cobalt, iron, etc. However, Pd(OAc) 2 ‐based catalytic systems make up the absolute majority in C−H/C−H coupling reactions promoting fusion of wide range of arenes and heteroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently many studies have been dedicated to oxidative C−H/C−H cross‐coupling of arenes. The coupling is catalysed by different transition metal complexes including rhodium, ruthenium, platinum, gold, copper, cobalt, iron, etc. However, Pd(OAc) 2 ‐based catalytic systems make up the absolute majority in C−H/C−H coupling reactions promoting fusion of wide range of arenes and heteroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, Zhang developed a mild and efficient method for the coupling of benzamides with oximes, which involves the aerobic oxidative coupling strategy (Scheme 26). [55] This reaction used Co(OAc) 2 . 4H 2 O catalyst along with a catalytic amount of Mn(III) oxidant in the presence of air.…”
Section: Arene‐arene Couplingmentioning
confidence: 99%
“…Fan et al demonstrated the use of fractal patterns of various types for epidermal electronics and RF applications (Figure 11b) [188] . The Archimedean spiral structure theorized by Lv et al in 2014 [189] is a stretchable spring design that can provide higher stretchability for the same areal coverage and contour length (Figure 11c). …”
Section: Fractal Serpentine Structuresmentioning
confidence: 99%
“…Reprinted by permission from Macmillan Publishers Ltd: Nature Communications [188] , copyright 2014; (c) Archimedean spiral theory design and plot. Reprinted from [189] , with permission from Elsevier; (d) Stretchable far-field…”
Section: List Ofmentioning
confidence: 99%